PROJECT MANAGEMENT EXPERT SYSTEM WITH ADVANCED DOCUMENT MANAGEMENT FOR PUBLIC INSTITUTIONS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This paper addresses public institutions' logistical challenges, focusing on project tracking and transparency. One challenging aspect of this endeavor is maintaining a clear and transparent record of ongoing projects while ensuring effective communication with all relevant stakeholders. Using machine learning and a comprehensive set of tools (to eliminate repetitive, time-consuming tasks), institutions can more efficiently manage and track projects with reduced manpower and fewer resources.
Keywords: Machine Learning; Smart Dispatching; Real-Time Resource Allocation; Advanced Document Management System; Routing algorithm; Resource optimization; Geographic information system (GIS); Traffic management